2011
DOI: 10.1111/j.1365-2214.2011.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk groups for sports injuries among adolescents - representative German national data

Abstract: In comparison with other results for developed countries, the incidence seems rather high. It remains to be clarified whether this is because of our use of more accurate population-based data. The results suggest that while developing preventive measures, the interaction between preferences for high-risk sports and physical as well as psychological development has to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
(52 reference statements)
1
4
0
1
Order By: Relevance
“…These results are in contrast with Nelson and Gordon-Larsen who found that adolescents who performed at least 5 bouts per week of moderate-to-vigorous physical activity were less likely to engage in health-related risk behaviors, and Pate et al who reported that less active adolescents had higher alcohol and marijuana use, cigarette smoking and wore seatbelt less frequently than more active adolescents [3,23]. The present results add to the body of literature that links PA to violent behaviour, alcohol consumption and increased occurrence of injuries [24][25][26][27]44].…”
Section: Discussionsupporting
confidence: 65%
“…These results are in contrast with Nelson and Gordon-Larsen who found that adolescents who performed at least 5 bouts per week of moderate-to-vigorous physical activity were less likely to engage in health-related risk behaviors, and Pate et al who reported that less active adolescents had higher alcohol and marijuana use, cigarette smoking and wore seatbelt less frequently than more active adolescents [3,23]. The present results add to the body of literature that links PA to violent behaviour, alcohol consumption and increased occurrence of injuries [24][25][26][27]44].…”
Section: Discussionsupporting
confidence: 65%
“…Sports participation has multiple benefits on children’s psychological, physical and social capabilities (Eime et al, 2013); however, with recent increases in sports participation (Eime et al, 2016), injuries have become an important pediatric public health issue. Population-based studies have reported that yearly between 3% and 8% of children experience sports-related injuries (Bruhmann & Schneider, 2011; Sheu et al, 2016), and recent studies have indicated that sport-related injuries represent one third of all emergency department (ED) visits among school-age children (Harmon et al, 2018) and occur five times more frequently than those caused by injuries from road accidents (Finch et al, 2014). They are also the second most common cause of severe injuries such as traumatic brain or spinal cord in children over 10 years of age (Oliver et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for physical activity related injuries in child populations have been identified (11). Non-modifiable factors, such as gender and age (4,20), and modifiable factors such as physical fatigue (12), overweight (19), collisions and falls (32), decreased proprioception and…”
Section: Introductionmentioning
confidence: 99%